The mouse attentional set-shifting task: A method for assaying successful cognitive aging? - YOUNG, Jared W (2010)
Humans exhibit considerable variance in cognitive decline with age, with some exhibiting little disruption while others become significantly impaired. In aged rodents, individual differences in spatial memory have been used to identify putative compensatory mechanisms underlying successful hippocampal aging. However, there are few parallel rodent models of cognitive decline in frontal cortex-mediated functions. We tested the hypothesis that, like aged humans, aged mice would exhibit greater variance in executive function measures compared to young mice. We examined the performance of young and aged C57BL/6N mice in the attentional set-shifting task. While young and old mice did not differ on trials to criterion performance, aged mice exhibited significantly greater variance in mean correct latency – selective to the extradimensional shifting stage – compared to their younger counterparts. Thus this task may be used to identify mechanisms underlying individual differences in decline of frontal-mediated performances with age.